Relationship of prenatal care to the Health Coordinators of the Child a cross-sectional study in San Joaquin, Iloilo - Balogo, Philip G.; Bomediano, Ma. Jonaah R.; Esparagoza, Marevi T.; Gallo, Czareena, Anne M.; Mallari, Maria Katerina (2015.)
Adequate prenatal care of pregnant mothers may affect and complete the immunizations of the children. Millennium Development Goal 4 and 5 set the desired improvement in maternal and child health which adequate and quality prenatal care can greatly affect. This study aims to determine the relationship of prenatal care the health indicators of the child in San Joaquin, Iloilo.
Research Project - Bachelor of Science in Public Health. University of the Philippines Visayas, Miagao,Iloilo
Keywords: Prenatal care -- San Joaquin; Mothers -- pregnant